Bucharest Drivers’ Perception of Navigation Apps and their Impact on Road Traffic (GeoPatterns, 2024)
Bucharest is one of the most affected cities in the world in terms of road traffic congestion and under these conditions, drivers are constantly looking for new strategies to help them cope with daily traffic. They are increasingly relying on more on navigation applications installed in their smartphones with GPS capabilities. This research aims to investigate drivers’ perception of the waythey use navigation applications and their purpose, especially Waze, their perception of the impact of these applications on traffic and the city or even on socialization (socialization through the application or the socializing effects of the application itself). The study conducted in 2018 reveals the positive perception of the impact that the application has and highlights its new affordance, drivers using it as a socialization tool, a utility that was not initially intended.